Effect of paediatric early warning systems (PEWS) implementation on clinical deterioration event mortality among children with cancer in resource-limited hospitals in Latin America: a prospective, multicentre cohort study - Agulnik, Asya (2023)
Background: Paediatric early warning systems (PEWS) aid in the early identification of clinical deterioration events in children admitted to hospital. We aimed to investigate the effect of PEWS implementation on mortality due to clinical deterioration in children with cancer in 32 resource-limited hospitals across Latin America. Methods: Proyecto Escala de Valoración de Alerta Temprana (Proyecto EVAT) is a quality improvement collaborative to implement PEWS in hospitals providing childhood cancer care. In this prospective, multicentre cohort study, centres joining Proyecto EVAT and completing PEWS implementation between April 1, 2017, and May 31, 2021, prospectively tracked clinical deterioration events and monthly inpatient-days in children admitted to hospital with cancer. De-identified registry data reported between April 17, 2017, and Nov 30, 2021, from all hospitals were included in analyses; children with limitations on escalation of care were excluded. The primary outcome was clinical deterioration event mortality. Incidence rate ratios (IRRs) were used to compare clinical deterioration event mortality before and after PEWS implementation; multivariable analyses assessed the correlation between clinical deterioration event mortality and centre characteristics. Findings: Between April 1, 2017, and May 31, 2021, 32 paediatric oncology centres from 11 countries in Latin America successfully implemented PEWS through Proyecto EVAT; these centres documented 2020 clinical deterioration events in 1651 patients over 556 400 inpatient-days. Overall clinical deterioration event mortality was 32·9% (664 of 2020 events). The median age of patients with clinical deterioration events was 8·5 years (IQR 3·9–13·2), and 1095 (54·2%) of 2020 clinical deterioration events were reported in male patients; data on race or ethnicity were not collected. Data were reported per centre for a median of 12 months (IQR 10–13) before PEWS implementation and 18 months (16–18) after PEWS implementation. The mortality rate due to a clinical deterioration event was 1·33 events per 1000 patient-days before PEWS implementation and 1·09 events per 1000 patient-days after PEWS implementation (IRR 0·82 [95% CI 0·69–0·97]; p=0·021). In the multivariable analysis of centre characteristics, higher clinical deterioration event mortality rates before PEWS implementation (IRR 1·32 [95% CI 1·22–1·43]; p<0·0001), being a teaching hospital (1·18 [1·09–1·27]; p<0·0001), not having a separate paediatric haematology-oncology unit (1·38 [1·21–1·57]; p<0·0001), and having fewer PEWS omissions (0·95 [0·92–0·99]; p=0·0091) were associated with a greater reduction in clinical deterioration event mortality after PEWS implementation; no association was found with country income level (IRR 0·86 [95% CI 0·68–1·09]; p=0·22) or clinical deterioration event rates before PEWS implementation (1·04 [0·97–1·12]; p=0·29). Interpretation: PEWS implementation was associated with reduced clinical deterioration event mortality in paediatric patients with cancer across 32 resource-limited hospitals in Latin America. These data support the use of PEWS as an effective evidence-based intervention to reduce disparities in global survival for children with cancer. Funding: American Lebanese Syrian Associated Charities, US National Institutes of Health, and Conquer Cancer Foundation. Translations: For the Spanish and Portuguese translations of the abstract see Supplementary Materials section.